Neurosarcoidosis: Frozen section rescue for a big mimicker - A case report - Farhan A Siddiqui; Jawad Al-Khalaf; Yusef Al-Marzooq; Jaffer Al-Obaid; Abdulhakim Y M. Almarzooq (Wolters Kluwer Medknow Publications, 2024)
Neurosarcoidosis is an uncommon but potentially serious manifestation of sarcoidosis. Diagnosis may be particularly challenging especially when neurosarcoidosis occurs in isolation or is the initial presentation of the systemic disease. The authors take this opportunity to report a case of neurosarcoidosis, presenting as the first manifestation of the disease, diagnosed on frozen section, occurring in a 43-year-old male patient with no past history or manifestation of sarcoidosis.